Factor Affecting Brand Switching Behavior and Brand Preference towards Mobile Phones in Kathmandu Valley - Bachhar, Shikshant; Shrestha, Pranoy (Nepalese Journal of Management, 2025)
This study examines the factors affecting brand switching behavior and brand preference towards mobile phones in Kathmandu Valley. Brand switching behavior is the dependent variable. The selected independent variables are price, brand image, product performance, product quality and availability. The primary sources of data is used to assess the opinions of respondents regarding price, brand image, product performance, product quality, availability and brand switching behavior. The study is based on the primary data of 153 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the factors affecting brand switching behavior and brand preference towards mobile phones in Kathmandu Valley. The study showed a positive impact of price on brand switching behavior. It indicates that affordable price leads to change in brand switching behavior. Similarly, the study showed a negative impact of brand image on brand switching behavior. It indicates that higher the brand image, lower would be the brand switching behavior. Likewise, the study showed a negative impact of product quality on brand switching behavior. It indicates that higher the product quality, lower would be the brand switching behavior. Further, the study also showed a negative impact of product performance on brand switching behavior. It indicates that higher the product performance, lower would be the brand switching behavior. It indicates that easily availability of product leads to decrease in brand switching behavior.